2021
DOI: 10.3390/ijerph182413073
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and the Crisis: Impacts of COVID-19 on Active Living and Life Satisfaction in Austria

Abstract: The COVID-19 pandemic has dramatically impacted human lifestyles across the world. Lockdowns and home confinement decreased prior opportunities for everyday physical activity. To retrospectively assess how the Austrian population coped with these aspects of the crisis, we conducted a cross-sectional online survey from March to September 2021 using a structured questionnaire in German. In total, 1214 participants (56.9% females, mean age 37.0 years) living across Austria shared self-reported information on soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…An international survey launched in April 2020, found relative reductions of 18% for this item and 16% for the total score of life satisfaction (Ammar et al, 2020b ), and an Austrian survey launched in March 2021, found decreases of −26% for this item's score and −20% for the total score life satisfaction (Jungwirth et al, 2021 ). Physical inactivity due to lockdowns, self-isolation, quarantine, homeschooling, and homeworking not only impacted fitness levels; but decreased scores in life satisfaction are commonly found in studies internationally (Ammar et al, 2020a , b ; Zhang et al, 2020 ; Eek et al, 2021 ; Jungwirth et al, 2021 ). Zhang and co-workers found life satisfaction decreases and distress increases in working people in China due to the exceptional disruptions of lives and work caused by COVID-19 (Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An international survey launched in April 2020, found relative reductions of 18% for this item and 16% for the total score of life satisfaction (Ammar et al, 2020b ), and an Austrian survey launched in March 2021, found decreases of −26% for this item's score and −20% for the total score life satisfaction (Jungwirth et al, 2021 ). Physical inactivity due to lockdowns, self-isolation, quarantine, homeschooling, and homeworking not only impacted fitness levels; but decreased scores in life satisfaction are commonly found in studies internationally (Ammar et al, 2020a , b ; Zhang et al, 2020 ; Eek et al, 2021 ; Jungwirth et al, 2021 ). Zhang and co-workers found life satisfaction decreases and distress increases in working people in China due to the exceptional disruptions of lives and work caused by COVID-19 (Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants rated six reasons for being outdoors (urge to move, recreation, social contacts, physical health, mental health, and distraction) before and during the COVID-19 pandemic on a 5-point Likert scale (1: strongly disagree, 2: disagree, 3: neutral, 4: agree, and 5: strongly agree) (Jungwirth et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations